Persistent Primitive Trigeminal Artery – A Rare Vessel - Das, Uddalok; Pandit, Narayan (Nepal Journal of Neuroscience, 2022)
Primitive carotido vertebral anastomosis is a well-recognized entity. During intrauterine development, craniovertebral blood circulation is characterized by temporary connections between the primitive internal carotid and dorsal longitudinal neural arteries. With normal development, they regress in the prenatal period. The most common of these is a persistent primitive trigeminal artery (PPTA) We report the case of a young male patient with intracranial bleed in the left capsuloganglionic region who was subsequently found to have a persistent primitive trigeminal artery on Magnetic Resonance Imaging Angiography.